2014
DOI: 10.7555/jbr.28.20130160
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between brachial-ankle pulse wave velocity and metabolic syndrome components in a Chinese population

Abstract: The purpose of this study was to assess the relationship between arterial stiffness, as measured by brachial-ankle pulse wave velocity (baPWV), and the presence of the metabolic syndrome (MS) in a Chinese population. A total of 4,445 subjects were enrolled. The prevalence of MS in our study population was 21.7%, 17.2% and 25.6% for the general population, males and females, respectively. With adjustments for age, gender, cigarette smoking, heart rate, total cholesterol, low-density lipoprotein (LDL) cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Scuteri et al [52] reported the impact of MetS on arterial stiffness to be similar in both sexes, and in this study, the number of MetS components associated with arterial stiffness measures was greater in males. However, baPWV and CAVI increased proportionally as the number of components increased in females, which occurred in other studies conducted on Asian populations [7, 8, 23, 25], but not in males. The different characteristics of the populations analyzed and the arterial stiffness measurement based on different parameters may explain these discrepancies.…”
Section: Discussionmentioning
confidence: 57%
“…Scuteri et al [52] reported the impact of MetS on arterial stiffness to be similar in both sexes, and in this study, the number of MetS components associated with arterial stiffness measures was greater in males. However, baPWV and CAVI increased proportionally as the number of components increased in females, which occurred in other studies conducted on Asian populations [7, 8, 23, 25], but not in males. The different characteristics of the populations analyzed and the arterial stiffness measurement based on different parameters may explain these discrepancies.…”
Section: Discussionmentioning
confidence: 57%
“…The influencing factors of baPWV are rather complicated. Numbers of metabolic syndrome components, 22 body size phenotypes, 23 ageing and male gender, 24 aerobic exercise and smoking 25 as well as BP control 26 were reported to impact on baPWV. Therefore, evaluating the effect of each factor is difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is a pre-atherosclerotic state which involves a cluster of factors, such as abdominal obesity, arterial hypertension, dyslipidemia, and hyperglycemia, and is closely associated with a marked increase in the risk of cardio-cerebrovascular diseases and type 2 diabetes mellitus [13]. Some studies have shown that MetS is correlated with arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%